Home bounded - global outreach: Home-based workers in Turkey - Saniye Dedeoæglu (International Labour Organization (ILO), 2020)
This report focuses on two categories of home-based workers in Turkey; industrial home-based pieceworkers and IT-enabled remote workers, who are commonly referred to in Turkey as 'freelancers'. With an aim of exploring the current patterns and issues of these two categories of home-based workers in Turkey, the report presents the situation and working practices of industrial home-based workers and freelance remote workers. A supply-and-demand side analysis is used to analyse the changes in the production networks and in the working relations. Issues such as access to work, working arrangements, working hours, earnings, health and safety and work-life balance are main areas of investigation. The interviews conducted in Istanbul with homeworkers reveal that an analysis of gendered nature of home-based work is necessary to unveil the values attached to piecework and digital remote work and that even social, cultural and economic distinctions between two groups, the lack of job security and decent working conditions as well as low bargaining power have resulted in their increased vulnerabilities in the Turkish labour markets.
Keywords: 330; self employment; non-standard forms of employment; telework; work at home; informal economy; gender equality